2008
DOI: 10.1007/s00429-008-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrinergic afferents and cytology of the macaque monkey midline, mediodorsal, and intralaminar thalamic nuclei

Abstract: The midline and intralaminar thalamic nuclei (MITN), locus coeruleus (LC) and cingulate cortex contain nociceptive neurons. The MITN that project to cingulate cortex have a prominent innervation by norepinephrinergic axons primarily originating from the LC. The hypothesis explored in this study is that MITN neurons that project to cingulate cortex receive a disproportionately high LC input that may modulate nociceptive afferent flow into the forebrain. Ten cynomolgus monkeys were evaluated for dopamine-beta hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 57 publications
1
40
0
1
Order By: Relevance
“…In addition, we have previously shown that lesions of the PVT affected the expression of PCA behavior, while damage to the surrounding area in the absence of PVT damage did not appear to affect PCA performance (Haight et al, 2015), supporting the idea that it is indeed PVT afferents, and not afferents to nearby nuclei, that were activated by stimulus presentation in the current study. Furthermore, the areas chosen for quantification showed retrograde labeling similar to previously published findings (Chen and Su, 1990, Van der Werf et al, 2002, Kirouac et al, 2005, 2006, Vogt et al, 2008, Hsu and Price, 2009, Li and Kirouac, 2012, Li et al, 2014). …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, we have previously shown that lesions of the PVT affected the expression of PCA behavior, while damage to the surrounding area in the absence of PVT damage did not appear to affect PCA performance (Haight et al, 2015), supporting the idea that it is indeed PVT afferents, and not afferents to nearby nuclei, that were activated by stimulus presentation in the current study. Furthermore, the areas chosen for quantification showed retrograde labeling similar to previously published findings (Chen and Su, 1990, Van der Werf et al, 2002, Kirouac et al, 2005, 2006, Vogt et al, 2008, Hsu and Price, 2009, Li and Kirouac, 2012, Li et al, 2014). …”
Section: Resultssupporting
confidence: 84%
“…Specifically, the PVT receives dense cortical input from much of the anterior-posterior gradient of the PrL, as well as the infralimbic (IL) and cingulate cortices (Vertes, 2004, Li and Kirouac, 2012). Subcortical afferents are widely distributed, and arise from the hypothalamus, ventral subiculum (vSub), and the central and medial amygdala, among other areas (Chen and Su, 1990, Canteras et al, 1995, Van der Werf et al, 2002, Kirouac et al, 2005, 2006, Vogt et al, 2008, Hsu and Price, 2009, Li and Kirouac, 2012, Li et al, 2014, Lee et al, 2015). In addition to its diverse inputs, the PVT sends efferent fibers to a variety of cortical and subcortical structures, including the PrL and IL, NAc core and shell, parts of the bed nucleus of the stria terminalis, and the central and basolateral amygdala, among other areas (Jones et al, 1989, Berendse and Groenewegen, 1990, Su and Bentivoglio, 1990, Moga et al, 1995, Van der Werf et al, 2002, Pinto et al, 2003, Parsons et al, 2006, Parsons et al, 2007, Li and Kirouac, 2008, Vertes and Hoover, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PVT receives a dense aminergic innervation from the brain stem: adrenergic innervation from the medulla oblongata (Otake and Ruggiero, 1995;Phillipson and Bohn, 1994), noradrenergic fibers from the locus coeruleus (Jones and Yang, 1985;Krout et al, 2002;Vogt et al, 2008), serotonergic innervation from the median and dorsal raphe (Cropper et al, 1984;de Medeiros Silva et al, 2014;Hsu and Price, 2009;Otake and Ruggiero, 1995;Vertes et al, 2010), dopaminergic fibers which derive primarily from cells of the periventricular and posterior hypothalamic areas (GarcĂ­a-Cabezas et al, 2007Hökfelt et al, 1976;Otake and Ruggiero, 1995;Takada et al, 1990). The aminergic innervation of PVT includes histaminergic fibers deriving from the tuberomammillary nucleus of the posterior hypothalamus (Airaksinen and Panula, 1988;Airaksinen et al, 1989;Jin et al, 2002;Panula et al, 1989).…”
Section: Inputs: the Busy Corridor Of The Thalamic Midlinementioning
confidence: 96%
“…Another basal ganglia target of NE afferents in rodents is the STN (Arcos et al, 2003; Belujon et al, 2007). Despite some advances in knowledge of the anatomy and physiology of NE in the rodent ventral midbrain and STN, much remains to be known about these interactions in primates (Ginsberg et al, 1993; Liprando et al, 2004; Vogt et al, 2008). …”
Section: Introductionmentioning
confidence: 99%